KINERJA PEGAWAI DI KANTOR CAMAT PINEMBANI KABUPATEN DONGGALA - Ahmad, Ahmad (Katalogis, 2016)
This study is to examine the performance of employees at the district office Pinembani Donggala regency. type of research is descriptive qualitative. Data types using primary data and secondary data. Data collection techniques, is done through observation, interviews, documentation and triangulation. Taking Informants using purposive sampling technique. Data analysis technique used is Robbins theory consisting of three (3) aspects of motivation, ability and opportunity. Based on the results of research, it is known that the performance of employees at the district office Pinembani yet effective and maximum. The cause is still a lack of motivation from the inside of employees, thus affecting low employee discipline. In addition, other factors that cause so that employees are violating the rules of the organization, in the absence of strict sanctions that are given to employees who do not obey and abide by the rules. While the infrastructure is still very low, while the ability and knowledge of employees in collaborating in providing services to the community, not fully in accordance with the needs of the organization. But the opportunity to participate in training and continuing education to a higher level, always get a response from the leadership.